Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/acs.organomet.5b00366
|View full text |Cite
|
Sign up to set email alerts
|

Di- and Mononuclear Iron Complexes of N,C,S-Tridentate Ligands Containing an Aminopyridyl Group: Effect of the Pendant Amine Site on Catalytic Properties for Proton Reduction

Abstract: A series of diiron complexes of N,C,S-tridentate ligands containing a 6-, 5-, or 4-amino-2-pyridyl group, [{Fe(μ-L-κ 3 N,C,S)(CO) 2 }Fe(CO) 3 ] (2, L = o-apyBPT; 3, L = mapyBPT; 4, L = p-apyBPT), was synthesized: apyBPT is a doubly deprotonated form of 3′-(amino-2″-pyridyl)-1,1′-biphenyl-2-thiol. Complexes 2−4 were converted to the mononuclear iron(II) complexes trans-[Fe(L-κ 3 N,C,S)(CO)-(PMe 2 Ph) 2 ] (6, L = o-apyBPT; 7, L = m-apyBPT; 8, L = papyBPT). In 2 and 6, the o-amino group is close to Fe bound to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 61 publications
(97 reference statements)
1
16
0
Order By: Relevance
“…ORTEP drawings of (a) 2 and (b) 3 with thermal ellipsoids at 50% probability level.Hydrogen atoms, crystal solvents, and ethyl groups of P(OEt) 3 in are omitted for clarity. THF/n-hexane, as reported for 1 48,51. The crystal structures of 2 and 3 are depicted inFigure 2.Selected bond distances and angles of 2 and 3 are listed inTable 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ORTEP drawings of (a) 2 and (b) 3 with thermal ellipsoids at 50% probability level.Hydrogen atoms, crystal solvents, and ethyl groups of P(OEt) 3 in are omitted for clarity. THF/n-hexane, as reported for 1 48,51. The crystal structures of 2 and 3 are depicted inFigure 2.Selected bond distances and angles of 2 and 3 are listed inTable 1.…”
mentioning
confidence: 99%
“…[18][19][20] We recently reported the synthesis and properties of a novel iron complex with an N,C,Stridentate ligand, trans- [Fe(PyBPT) ), where PyBPT is a doubly deprotonated form of 3'-(2''-pyridyl)-1,1'-biphenyl-2-thiol formed via the C-S bond cleavage of the dibenzothiophene derivative. [48][49][50][51] The N,C,S-pincer iron(III) carbonyl complex exhibited unusual stability in solution under ambient conditions in the dark, while the CO ligand readily underwent substitution reaction with the coordinative solvent in response to the short wavelength region of visible light. 52 A theoretical study indicated that SOMO of the iron(III) carbonyl complex mainly consisted of the dπ orbital of the central iron and pπ orbital of the sulfur atom.…”
mentioning
confidence: 99%
“…The Fe(1)−C(8) bond distances for 1 (1.9456(18) Å) and 2 (1.956(3) Å) are similar to those of diiron complexes derived from PyDBT derivatives or QTs, 33,36,37 and the Fe(1)−C (18) bond trans to C(8) is ca. 0.05 Å longer than the Fe(1)−C (19) bond, indicating the trans influence of the central C donor of the N,C,S-tridentate ligands.…”
Section: ■ Results and Discussionmentioning
confidence: 59%
“…These findings suggest that complex 1 have a C,Sbridged dinuclear structure with the formula [{Fe(μ-qvbtκ 3 N,C,S)(CO) 2 }Fe(CO) 3 ] (Scheme 2), which is similar to that of diiron carbonyl complexes prepared from pyridyl-substituted dibenzothiophene (PyDBT) or quinolyl-substituted thiophenes (QTs). 33,36,37 In the 1 H NMR spectrum of 2, a significant downfield shift was observed for the quinoline CH adjacent to the vinyl group (7.50 ppm for 1, 9.08 ppm for 2), which is due to the C−H•••O(methoxy) short contact (mentioned later). Complexes 1 and 2 were structurally characterized by X-ray crystallography (Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
See 1 more Smart Citation